Neutrality Of The Acting Governor In The 2024 Presidential Election: Case Study Central Java - Jingga Savana Soeherman; Abdul Ghofur (UNIVERSITAS PAKUAN, 2026)
This study aims to analyze the neutrality of the Acting Governor of Central Java, Nana Sudjana, in the 2024 Presidential Election by highlighting the relationship between bureaucracy and electoral political interests. The study employs a qualitative method using a case study approach through interviews, documentation, and literature review. The results indicate that, normatively, there was no violation of neutrality, as evidenced by the absence of findings or official rulings from election oversight bodies. However, empirically, there were indications of implicit non-neutrality, such as bureaucratic mobilization, patronage relationships, and the use of state resources that could potentially influence public political preferences. Furthermore, interview results indicate that the appointment of the Acting Governor, although legally valid, was not free from considerations of loyalty and the central government’s political agenda. The limitations of oversight institutions in addressing latent political practices further exacerbate the gap between norms and reality.